1999
DOI: 10.1002/(sici)1521-3862(199903)5:2<59::aid-cvde59>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD of Platinum (100) Films on Random Hastelloy C276

Abstract: Platinum metal films find applications in a wide range of technologies such as contacts in microelectronic devices, [1]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Though widely studied, one major drawback of (C 5 H 4 Me)­PtMe 3 as a CVD precursor is that it suffers from long nucleation delays. ,,,, This problem can be traced to the high metal–ligand bond strengths and consequent high kinetic barriers associated with eliminating ligands from adsorbed (C 5 H 4 Me)­PtMe 3 molecules. , Such elimination reactions typically occur more quickly on platinum surfaces than they do on the underlying substrate, owing to the highly catalytic nature of platinum. ,, As a result, deposition initiates to form islands on the surface, which subsequently grow rapidly. Similar island growth behavior has been observed for several other Pt CVD precursors. , Eventually, the islands coalesce, but the long nucleation delays, and resulting sparse nucleation, mean that it is difficult to make continuous films that are also very thin; instead, at the point of full coalescence, the films are typically relatively thick and rough. Although the deposition of conformal Pt films has been achieved by means of an alternating ALD/oxygen plasma process from (C 5 H 4 Me)­PtMe 3 , nucleation delays of ∼50 cycles are still observed …”
Section: Introductionsupporting
confidence: 63%
“…Though widely studied, one major drawback of (C 5 H 4 Me)­PtMe 3 as a CVD precursor is that it suffers from long nucleation delays. ,,,, This problem can be traced to the high metal–ligand bond strengths and consequent high kinetic barriers associated with eliminating ligands from adsorbed (C 5 H 4 Me)­PtMe 3 molecules. , Such elimination reactions typically occur more quickly on platinum surfaces than they do on the underlying substrate, owing to the highly catalytic nature of platinum. ,, As a result, deposition initiates to form islands on the surface, which subsequently grow rapidly. Similar island growth behavior has been observed for several other Pt CVD precursors. , Eventually, the islands coalesce, but the long nucleation delays, and resulting sparse nucleation, mean that it is difficult to make continuous films that are also very thin; instead, at the point of full coalescence, the films are typically relatively thick and rough. Although the deposition of conformal Pt films has been achieved by means of an alternating ALD/oxygen plasma process from (C 5 H 4 Me)­PtMe 3 , nucleation delays of ∼50 cycles are still observed …”
Section: Introductionsupporting
confidence: 63%
“…Pt layer is reported to be deposited by MOCVD below 395 o C from the literature [18][19], the present data show the possibility of the preparation of fatigue-free FeRAM capacitor by all-MOCVD process below 400 o C.…”
Section: Pzt Films Deposited At 395 O Csupporting
confidence: 58%
“…43) We have shown that oxygen is effective to avoid carbon incorporation into the films prepared from Pt(acac) 2 ; platinum films of high-purity and an attractive epitaxial or oriented nature can be grown by an appropriate addition of oxygen. [19][20][21]44) Epitaxial platinum films on insulating substrates are of interest in device processing to achieve epitaxial growth of functional ceramic over-layers as well as in fundamental conductivity studies. Epitaxial platinum films grown by CVD effectively promoted the epitaxial growth of AlN over-layers.…”
Section: -Diketonate Platinum Complexesmentioning
confidence: 99%